Serenity in Political Uncertainty - Doumit, Rita (2015)
College students are often faced with academic and personal stressors that threaten their well-being. Added to that may be political and environmental stressors such as acts of violence on the streets, interruptions in schooling, car bombings, targeted religious intimidations, financial hardship, and uncertainty of obtaining a job after graduation. Research on how college students adapt to the latter stressors is limited. The aims of this study were (1) to investigate the associations between stress, uncertainty, resilience, social support, withdrawal coping, and well-being for Lebanese youth during their first year of college and (2) to determine whether these variables predicted well-being. A sample of 293 first-year students enrolled in a private university in Lebanon completed a self-reported questionnaire in the classroom setting. The mean age of sample participants was 18.1 years, with nearly an equal percentage of males and females (53.2% vs 46.8%), who lived with their family (92.5%), and whose family reported high income levels (68.4%). Multiple regression analyses revealed that best determinants of well-being are resilience, uncertainty, social support, and gender that accounted for 54.1% of the variance. Despite living in an environment of frequent violence and political uncertainty, Lebanese youth in this study have a strong sense of well-being and are able to go on with their lives. This research adds to our understanding on how adolescents can adapt to stressors of frequent violence and political uncertainty. Further research is recommended to understand the mechanisms through which young people cope with political uncertainty and violence.